Polish hematology on the Internet - Szymczyk, Agnieszka; Macheta, Arkadiusz; Radko, Katarzyna; Muzyka, Justyna; Podhorecka, Monika (Polish Journal of Public Health, 2016)
The end of 20th and the beginning of 21st century have brought an intense development of the IT applications, without which people cannot imagine life. In the last years, the Internet has been playing more and more crucial role. It has become a valuable source of information for a big group of people, both patients and medical staff. Pharmaceutical syndicates, scientific units, magazines, medical clinics and departments, as well as individuals design their own websites. This article introduces a review of the most important websites about hematology.